HARDINESS DAN ADAPTABILITAS KARIR - Desia Wahyu Febrianingrum; Doddy Hendro Wibowo (Program Studi Psikologi Universitas Malahayati, 2021)
ABSTRACT: HARDINESS AND CAREER ADAPTABILITY Career adaptability is needed to assist students in facing and anticipating the challenges that may occur in entering the world of work. This study aims to determine the relationship between hardiness and career adaptability in vocational students. This study used a sample of 113 people who were students of class XII using the saturated sample technique. The measuring instruments used in this study are the Career Adapt-Abilities Scale (CAAS) and the Dispositional Resilience Scale (DSR-15). The data analysis technique used is the Pearson product moment correlation technique which shows the correlation coefficient value of 0.952 (p < .001). So it can be interpreted that there is a significant positive relationship between hardiness and career adaptability of SMK